Analysis Influence of Price, Service and Process on Consumer Interest Rahn - Ali Azis Usman Harahap (Jurnal Investasi Islam, 2025)
This study investigates the influence of price, service quality, and the pawn process on public interest in Rahn (gold pawning) products at PT Bank Aceh Syariah using a quantitative approach. The findings indicate that service quality and the pawn process are key drivers of public interest, while price is less influential. High-quality service and a pawn process that is simple, fast, and efficient encourage greater customer engagement with Rahn products. Collectively, these variables influence public interest, with service quality and operational efficiency emerging as the most dominant factors. The results suggest that convenience and procedural efficiency play a more decisive role than cost considerations in shaping customer decisions. Overall, improving service quality and optimizing operational processes are more effective strategies for increasing public interest in Rahn products than focusing solely on pricing.